Reducing the interfacial defect density of CZTSSe solar cells by Mn substitution - Lie, Stener (2020)
Cation disorder which arises from the size and chemical environment similarity of Cu and Zn is the limiting factor in Cu2ZnSnSxSe4−x (CZTSSe) performance. Cation substitution is one effective way to solve this issue, however, the most commonly reported substitutes, Ag and Cd, are not ideal as they detract from the earth-abundant and non-toxic motivation of CZTSSe. Mn is a promising candidate in comparison with other candidates (e.g. Fe, Ni or Co), because of its oxidation state stability and larger ionic size mismatch with Cu. In this study, Cu2MnxZn1−xSn(S,Se)4 (CMZTSSe) thin film solar cells were prepared by chemical spray pyrolysis and a subsequent selenization process. We study the influence of Mn substitution on the morphological, structural, optical, electrical and device properties. A distinct phase transformation from CZTSSe kesterite to C(M,Z)TSSe stannite is observed at 20% Mn substitution. A high amount of Mn substitution (x ≥ 0.6) is shown to increase the carrier density significantly which introduces more defects and non-radiative carrier recombination as shown by quenched photoluminescence intensity. Consequently, reduction in device performance is observed for these samples. The highest power conversion efficiency is achieved at x ≈ 0.05 with η = 7.59%, Voc = 0.43 V, Jsc = 28.9 mA cm−2 and FF = 61.03%. The improved open circuit voltage (Voc) and fill factor (FF) are attributed to the improved shunt resistance and carrier transport due to low defect density especially at the CdS/CMZTSSe interface. Finally, based on our electrical characterization, a few suggestions to improve the efficiency are proposed.